In Vitro Effect of temperature on dentin bond strength of universal adhesive systems = Efecto In Vitro de la temperatura sobre la resistencia de unión de los sistemas adhesivos universales a la dentina - Akarsu, Serdar; Aktuğ Karademir, Sultan (2020)
The aim of this study was to evaluate the shear bond strength (SBS) of two universal adhesives (Universal Single Bond and All Bond Universal) and a two-step self-etch adhesive system (Clearfil SE Bond) to dentine at various temperatures. Materials and Methods: One hundred and twenty dentin specimens were divided randomly to 12 groups, according to adhesive systems (Universal Single Bond and All Bond Universal, Clearfil SE Bond) and temperature (4ºC, 20 ºC, 36ºC, 55ºC) used. Dentin specimens were prepared (n :10, adhesives were applied, and composite cylinders were polymerized. Statistical analysis of the SBS data was performed using Two-way analysis of variance (ANOVA) and Tukey's Honestly Significant Differences post-hoc test. Results: The Clearfil SE Bond was shown to have higher SBS than the universal adhesives at all temperatures; however, there was no statistically significant difference (P>0.05). In both groups, the lowest SBS values were observed in the samples at 4°C while the highest SBS values were observed in the samples at 55°C. In this case, there was a statistically significant difference (P<0.05). Conclusions: The results suggest that the effectiveness of an adhesive may increase if it is preheated at 36°C or above before use instead of being used immediately after removal from the refrigerator or at room temperature.
El objetivo de este estudio fue evaluar la resistencia al cizallamiento (SBS) de dos adhesivos universales (Universal Single Bond y All Bond Universal) y un sistema de adhesivo de autograbado de dos pasos (Clearfil SE Bond) a la dentina en diferentes temperaturas. Materiales y métodos: Ciento veinte muestras de dentina se dividieron aleatoriamente en 12 grupos, de acuerdo con los sistemas adhesivos (Universal Single Bond y All Bond Universal, Clearfil SE Bond) y la temperatura (4ºC, 20ºC, 36ºC, 55ºC) utilizada. Se prepararon muestras de dentina (n: 10), se aplicaron los sistemas adhesivos y se polimerizaron los cilindros compuestos. El análisis estadístico de los datos de SBS se realizó utilizando el análisis de varianza de dos vías (ANOVA) y la prueba post-hoc de Tukey's. Resultados: El Clearfil SE Bond mostró tener un SBS más alto que los adhesivos universales en todas las temperaturas evaluadas; sin embargo, no hubo una diferencia estadísticamente significativa (P> 0.05). En todos los grupos, los valores más bajos de SBS se observaron en las muestras a 4°C, mientras que los valores de SBS más altos fueron obtenidos en las muestras a 55°C (P <0.05). Conclusiones: Los resultados sugieren que la efectividad de un adhesivo puede aumentar si se precalienta a 36°C o superior, antes de usarlo inmediatamente después de sacarlo del refrigerador o a temperatura ambiente.
En revista Odóvtos, vol. 22, no. 1 (enero-abril 2020)
Descripción basada en el contenido visto el 26 de septiembre, 2024
También disponible en formato HTML y EPUB